1997
DOI: 10.1038/bjc.1997.256
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p53 protein during pancreatitis

Abstract: Summary Overexpression of p53 correlates with neoplasia in many cytological specimens. To test the specificity of overexpressed p53 as a tumour marker for the detection of pancreatic cancer, we analysed cytological specimens of pancreatic juice samples from patients with pancreatitis or pancreatic carcinoma (n = 42) for p53 protein overexpression. p53 protein overexpression was found in 59% of patients with pancreatitis and 67% of patients with pancreatic carcinoma. Thus, Kalthoff et al, 1993), and more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
1
23
1
Order By: Relevance
“…Immunocytology with p53 antibodies using cells from pancreatic duct brushings was shown by Iwao et al [169,181] to detect 36 out of 44 (82%) pancreatic carcinomas. Unfortunately, a similar analysis by Maacke et al [168] that confirmed this finding, in that 10 of 15 (67%) patients with pancreatic carcinoma had p53 over-expression in pancreatic cells obtained endoscopically, also found p53 over-expression in 16 of 27 (59%) patients with chronic pancreatitis. It is likely that p53 over-expression in the ductular cells of chronic pancreatitis represents increased p53 activity rather than a manifestation of TP53 mutations.…”
Section: Tp53 Tumour Suppressor Genesupporting
confidence: 54%
“…Immunocytology with p53 antibodies using cells from pancreatic duct brushings was shown by Iwao et al [169,181] to detect 36 out of 44 (82%) pancreatic carcinomas. Unfortunately, a similar analysis by Maacke et al [168] that confirmed this finding, in that 10 of 15 (67%) patients with pancreatic carcinoma had p53 over-expression in pancreatic cells obtained endoscopically, also found p53 over-expression in 16 of 27 (59%) patients with chronic pancreatitis. It is likely that p53 over-expression in the ductular cells of chronic pancreatitis represents increased p53 activity rather than a manifestation of TP53 mutations.…”
Section: Tp53 Tumour Suppressor Genesupporting
confidence: 54%
“…This, of course, could occur through an idiotypic network triggered by p53 autoimmunity [19,20]. The induction of the anti-p53 antibodies can be accounted for by the accumulation of the p53 molecule, not only in tumour cells [21], but also in activated inflammatory cells [22]. The accumulation of p53 apparently can trigger an autoimmune response to the molecule [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…First, in contrast to this study, false positive p53 stainings in be nign pancreatic lesions were demonstrated in previous studies at rates ranging from 3% to about 10% [12,13,26,27,[31][32][33] . Indeed, wild-type p53 over-expression can be inducible under certain benign conditions, such as during inflammation in response to TNF-alpha [34] . Second, this study showed a lower rate of p53 IH positivity in malignant cases: 29% versus the usual range of 50% to 70% in other EUS-FNA and biopsy series [13,14,32] .…”
Section: Discussionmentioning
confidence: 99%